#TITLE_ALTERNATIVE# - ANDAYANA (NIM : 132060910); Pembimbing: Prof. Dr. Ir. Tati Latifah Erawati Rajab Mengko; Prof. , ILMA
There are many kinds of microscopes, from the simple optical microscope consisting of two positive lenses, to the more complex microscope such as holography microscope and electron microscope. Holographic microscope utilize interference phenomenon that occurs between object beam and reference beam. The holographic interference was recorded using digital holographic microscope hardware. In this thesis, design and implementation of digital holographic microscope software used for reconstructing the hologram of a digital holographic microscope hardware off-axis configuration was proposed. The method proposed to reconstruct the hologram was Fourier transformation and Fresnel transformation. Fourier transformation was subjected to hologram so that will generate an image, called spectrum image, composed of three parts of the dominant frequency, that is zero order, and pair of conjuget dominant frequency called twin image. Then the spectrum was cut with the center of cutting in one of pair conjuget dominant frequency. Then the cut image was subjected to inverse Fourier transform before Fresnel transformation was done. The results of this Fresnel transformation can be displayed in its amplitude image only, phase only, or three-dimensional shape obtained from the phase information that has been unwrapped. This algorithm was used to reconstruct the holographic image of a holographic image of reference object and test object. Reference object that is used was a hologram of rat basophilic leukemia mast cell (RBL-2H3) which had size of 635x477 pixels. Based on MSE and PSNR between the reconstructed amlitude image and the amplitude image from literatur, it can be concluded that both picture was looked alike. This similarity indicated that the reconstruction algorithm was succed to reconstruct the object reference. Hologram of test object image obtained from digital holographic microscope hardware with off-axis configuration. The test results showed this reconstruction algorithm can also reconstruct the hologram of test object. However, holograms obtained from the hardware configuration of digital holographic microscope off-axis contained diffraction of other information beside result of interference between object beam and reference beam. Under several proposed solutions to eliminate this diffraction, solution that provided the best results was frequency value filtering.